2018
DOI: 10.1111/edt.12422
|View full text |Cite
|
Sign up to set email alerts
|

Mouthguard sheet temperature after heating

Abstract: The change of mouthguard sheet temperature during heating was different between ethylene vinyl acetate and polyolefin sheets. The ethylene vinyl acetate sheets maintained the vacuum-formed mouthguard thickness in comparison with the polyolefin sheets with a better fit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 24 publications
0
13
2
Order By: Relevance
“…This result suggests that the appropriate heating condition of polyolefin for the pressure formation should be different from that of ethylene vinyl acetate. The results of the previous study that investigated the change of sheet temperature in the vacuum former showed that the temperature of polyolefin sheet was about 100°C at the hanging distances of 10, 15, and 20 mm . The results of the previous study are different from the results of this study.…”
Section: Discussioncontrasting
confidence: 95%
See 4 more Smart Citations
“…This result suggests that the appropriate heating condition of polyolefin for the pressure formation should be different from that of ethylene vinyl acetate. The results of the previous study that investigated the change of sheet temperature in the vacuum former showed that the temperature of polyolefin sheet was about 100°C at the hanging distances of 10, 15, and 20 mm . The results of the previous study are different from the results of this study.…”
Section: Discussioncontrasting
confidence: 95%
“…The results of the previous study that investigated the change of sheet temperature in the vacuum former showed that the temperature of polyolefin sheet was about 100°C at the hanging distances of 10, 15, and 20 mm . The results of the previous study are different from the results of this study. The reason for this difference is likely to be due to the difference of the environment of heating.…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations